Hydro-disk-type of electrorheological brakes for small mobile robots. Issue 2 (6th August 2021) - Togawa, Takanori; Tachibana, Takuma; Tanaka, Yutaka; Peng, Jinghui
In micromouse competitions, small autonomous robots move in a maze and turn into corners with steep angles at high speeds. However, the recent competition was marked by speeding up. Generally, driving performance is limited through only the motor current control braking. Therefore, in this study, we developed a mechanical brake device using electrorheological fluid (ER fluid). Around the robot's drive, this brake device is connected to the DC motor through gears, and when the robot decelerates, the decelerating time is shortened if the ER brake is used together with the electric DC motor brake, so the deceleration time before a corner is shortened. Thus, the movement time from start of the maze to the goal is also shortened. Aiming at improving the performance of small robots that participate in micromouse competitions, we reported the basic research, performance evaluation, and brake design of a small brake that uses ER fluid.